Енергоаудит у системі енергоменеджменту підприємства - Акіншина, О. В.; Третякова, Л. І.; Антоненко, О. М. (Видавництво Львівської політехніки, 2012)
Розглядаються пріоритетні напрями енергетичної стратегії та політики енергозбереження промислових підприємств, досліджуються першочергові завдання щодо підвищення ефективності використання енергетичних ресурсів проведенням енергетичного аудиту, представлені інструментарій і порядок проведення енергоаудиту. The paper examines the priority directions of the Ukrainian energy saving policy as well as a potential for increase in energy efficiency of industrial production through the use of technological component of the energy-saving potential where more effective utilization of material and energy resources is achieved via introducing the energy audit. The stages and order of implementation of the energy audit are defined, including the compilation of balance of energy and material resources.
Energy audit in system of energemanagment
Keywords: політика енергозбереження; енергетичні ресурси; енергетичний аудит; потенціал енергозбереження; енергетичний паспорт; Energy policy; energy resources; energy audit; energy saving potential; the energy passport